Kalimat Subordinasi Bahasa Batak Toba: Kajian Tipologi Sintaksis - Annisah Inriani Harahap; Samuel Nugraha Cristy; Liao Chunliu; Mulyadi Mulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to describe the types of subordinate sentences in the Batak Toba language and test the pivot of the Toba Batak language in subordinating constructions. The data used is written data. The data is a combination of transitive clauses and substantive clauses contained in the book 'Turi-turian Ni Halak Batak'. This research is qualitative descriptive research. Data were analyzed using the agih method with changing and changing forms techniques. Replacement techniques are used to replace words in a sentence with words that have the same syntactic function. Meanwhile, the change of form technique is used to change the form of a word in a sentence into a different sentence form but still has the same syntactic function. The results of the research show that grammatically the Toba Batak language is included in the accusative language typology. The pivot test shows that the release of FN in the Toba Batak language can be done directly if the FN is in the S or A function. If the FN is in the P function the release cannot be done directly, but one of the clauses must be passivized or topicalized first. Based on this pattern, it can be concluded that the Toba Batak language is included in the accusative language type with an S/A pivot pattern.